2019
DOI: 10.5114/bta.2019.90238
|View full text |Cite
|
Sign up to set email alerts
|

Textile azo dye decolorization and detoxification using bacteria isolated from textile effluents

Abstract: Azo dyes, which are highly toxic, carcinogenic, and mutagenic for living organisms, are used as coloring chemicals in textile industries. Physicochemical methods used for removing azo dyes are expensive, can generate secondary waste, and are not very efficient. In this study, we used a biological approach to reduce the toxicity of three azo dyes, i.e., congo red, methyl orange, and reactive red 198, from textile effluents. Six dye-decolorizing bacteria were screened from waste water obtained from the textile i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…has also been reported to have the ability to remove 90% of Novacron Brilliant Blue color (Karim et al, 2018) . In addition, previous research showed that Pseudomonas aeruginosa and Staphylococcus aureus could decolorize congo red by 80% and 96%, respectively (Karnwal, 2019) Comamonas aquatica and Ralstonia mannitolilytica can also reduce methylene blue by 67.9% and 60.3%, respectively Siregar et al (2020) and Bacillus subtilis WG13 has also been reported to be able to remove 70% of direct red 23 colors (Thiruppathi et al, 2021) .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…has also been reported to have the ability to remove 90% of Novacron Brilliant Blue color (Karim et al, 2018) . In addition, previous research showed that Pseudomonas aeruginosa and Staphylococcus aureus could decolorize congo red by 80% and 96%, respectively (Karnwal, 2019) Comamonas aquatica and Ralstonia mannitolilytica can also reduce methylene blue by 67.9% and 60.3%, respectively Siregar et al (2020) and Bacillus subtilis WG13 has also been reported to be able to remove 70% of direct red 23 colors (Thiruppathi et al, 2021) .…”
Section: Introductionmentioning
confidence: 94%
“…However, Bacillus cereus in this same group has been tested for its ability to degrade synthetic dye. It can also decolorize synthetic dye, namely methyl orange by 75% with a concentration of 100 mg/L, at pH 7.2 and temperature 37°C, respectively, for 144 hours (Karnwal, 2019) . Bacillus subtilis can remove Direct violet color by 68.57% with a concentration of 20 mg/L at pH 7 and 28°C for 72 hours.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the remarkable roles of bacteria such as Staphylococcus hominus , Vibrio sp., Proteus vulgaris , Dietzia sp., Pseudomonas aeruginosa , Bacillus subtilis , Stenotrophomonas sp., and Halomonas sp. in efficient decolorization of dyes, and there are many other bacterial species that have developed their enzyme systems for degrading dye compounds (Mansur et al, 2017 ; Roy et al, 2018 ; Karnwal, 2019 ; Mandic et al, 2019 ). Bacteria possess multiple mechanisms to remove dyes, and because they are easy to use, they have advantages in terms of commercial value (Sarim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The decolorization of melanoidin compounds through microbial degradation has the potential to become an ecofriendly and cost-efficient alternative to the current methods of remediation of spent wash (Kumar et al, 1998;Moosvi et al, 2005;Naik et al, 2010). This is a good alternative to chemical treatment as an effective removal of melanoidin can be achieved using microorganisms (Karnwal, 2019). In the past decade, melanoidin degradation by bacteria and actinobacteria has received significant attention (Mohana et al, 2007).…”
Section: Introductionmentioning
confidence: 99%